Answer: x = -4
Step-by-step explanation: To solve for x in this equation, we want to get x by itself on the left side of the equation.
Since 6 is being subtracted from x, to get x by itself,
we need to add 6 to the left side of the equation.
If we add 6 to the left side, we must also add 6
to the right side to keep our equation balanced.
On the left, -6 and +6 cancel each other out so we are simply
left with x. On the right side, -10 + 6 equals -4.
So we have x = -4.
Finally, we can check our answer by substituting -4 back into
the original equation. So we have (-4) - 6 = -10 or -10 = -10.
Since -10 = -10, we know our answer, x = -4, is correct.